Barriers in collection sharing among libraries of Pakistan : university library managers’ viewpoint - Ameen, Kanwal (2021)
University libraries in Pakistan are a privileged type of libraries with comparatively sound collections and good staff strength. They spend a large portion of their funds on developing in-house collections in isolation. In spite of the prevailing information and communication technology (ICT), there is hardly any practice of sharing collections in a formal manner. Using a survey method, this study explores the barriers to collection sharing among the well established chartered university libraries situated in the major cities of Pakistan. The survey followed a qualitative design based on an interview technique of data collection. Twenty chief/head librarians from five major cities of Pakistan were interviewed. These in-depth, semi-structured interviews were conducted at the librarians’ workplaces during 2003 to 2004. The data analysis of the present study revealed that various technical, procedural, psychological, and behavioral barriers in achieving planned and meaningful collection-sharing (CS) programs still prevail. It suggests analyzing the possibilities, opportunities, and challenges of CS in the emerging paradigm. The findings and suggestions may be of value to developing countries with similar situations.